Quality of life after first-line cryoablation of atrial fibrillation: results from the Cryo AF Global Registry. (19th May 2022) - Zucchelli, G; Chun, KRJ; Khelae, SK; Foldesi, C; Kueffer, FJ; Van Bragt, K; Scazzuso, F; On, YK; Kandari, FA; Okumura, K
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): The registry was sponsored Medtronic, Inc., Minneapolis, MN. Background: Atrial fibrillation (AF), the most common cardiac arrhythmia, burdening patients with a myriad of symptoms. Three recent randomized trials demonstrated that cryoballoon ablation (CBA) is superior to antiarrhythmic drugs (AADs) as a first-line treatment for the prevention of arrhythmia reoccurrence in patients with paroxysmal AF. However, the global outcome of CBA performed according to local standard of care as a first-line therapy for AF is not reported. Purpose: To compare safety, efficacy, and quality of life outcomes in patients treated with CBA for first-line management of AF against patients treated with CBA following failed AAD therapy. Methods: The Cryo AF Global Registry, an ongoing, prospective, multicenter registry, of AF patients undergoing index CBA performed according to local standards at 58 centers in 26 countries worldwide. In this analysis, subjects undergoing first-line cryoablation were compared to patients who were refractory to AAD therapy and/or taking AADs at baseline. Safety was assessed utilizing a composite of serious procedure-related complications. To evaluate efficacy, time-to-first atrial fibrillation, -flutter and/or -tachycardia (AF/AFL/AT) recurrence post a 90-day blanking period was compared between groups using Kaplan-Meier estimates. Quality of life was evaluated using the EQ-5D-3L questionnaire at baseline and at 12 months following CBA. Log-rank, two-sample t-test, and exact binomial tests were utilized to test difference between groups. Results: Of 1, 394 total patients, 433 (31.1%) were drug naïve prior to CBA. Patients in the AAD therapy cohort failed a mean of 1.2 ± 0.5 AADs before CBA. Freedom from AF/AFL/AT recurrence at 12 months was 87.8% in first-line patients compared to 81.6% in AAD-refractory patients (p<0.01). Serious adverse event rates were not statistically different (p=0.32) between first-line (2.3%) and AAD-refractory (3.4%) patients. First-line CBA resulted in a larger mean decline in symptoms upon follow-up, with 81% of patients reported to be symptom-free at 12 months. Further, first-line patients were prescribed AADs at a lower rate at discharge (18.6% vs.62.8%) and at 12-months (9.7% vs.29.9%) in comparison to patients in the AAD cohort. However, cryoablation did result in AAD prescriptions being reduced by approximately 50% in both cohorts from discharge to 12-months. As determined by the EQ-5D-3L score, quality of life improved for patients in both groups, with no significant difference between first-line and AAD-refractory patients (p=0.29). Conclusion: This real-world global evaluation supports CBA as a safe and efficacious first-line treatment that improves the quality of life for patients with symptomatic AF.